Chain Rule
Chain Rule
Chain Rule
The Chain Rule allows us to use our knowledge of the derivatives of functions f (x) and
g(x) to find the derivative of the composition f (g(x)):
dy dy du
= .
dx du dx
Using alternative notation,
d
[f (g(x))] = f 0 (g(x))g 0 (x),
dx
d du
[f (u)] = f 0 (u) .
dx dx
Proof
The three formulations of the Chain Rule given here are identical in meaning. In words, the
derivative of f (g(x)) is the derivative of f , evaluated at g(x), multiplied by the derivative of
g(x).
Examples
d d d
[sin(2x 1)] = [sin(u)] [2x 1] f (x) = sin(x)
dx du dx
= cos(u) 2 g(x) = 2x 1
= 2 cos(2x 1). f (g(x)) = sin(2x 1)
8
To differentiate (3x2 4x + 1) , we identify u = 3x2 4x + 1. Then
d 2 d h 8i d h 2
8 i
3x 4x + 1 = u 3x 4x + 1 f (x) = x8
dx du dx
7
= 8u (6x 4) g(x) = 3x2 4x + 1
7 8
3x2 4x + 1
= 8(6x 4) 3x2 4x + 1 . f (g(x)) =
2
To differentiate ex , we identify u = x2 . Then
d h x2 i d u d h 2i
e = [e ] x f (x) = ex
dx du dx
= eu (2x) g(x) = x2
2
= 2xex .
2
f (g(x)) = ex
Sometimes you will need to apply the Chain Rule several times in order to differentiate a
function.
Example q
We will differentiate sin2 (3x) + x.
q h i
d
dx
sin2 (3x) + x = 1
d
dx
sin2 (3x) + x f (u) = u
2 sin2 (3x)+x
1
d
f (u) = u2
= 2 sin(3x) dx [sin(3x)] + 1 d
2 sin2 (3x)+x
dx
[x] = 1
= 1 d
2 sin(3x) cos(3x) dx [3x] + 1 f (u) = sin(u)
2 sin2 (3x)+x
= 1 (2 sin(3x) cos(3x) 3 + 1)
2 sin2 (3x)+x
6 sin(3x) cos(3x) + 1
= q
2 sin2 (3x) + x
Key Concepts